PENGARUH KUALITAS INFORMASI DAN TEKNOLOGI INFORMASI TERHADAP KINERJA RANTAI PASOK MELALUI PENERAPAN PEMBAGIAN INFORMASI - Vincent, Vincent; Laulita, Nasar Buntu (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
In this study, technological advances have encouraged the use of AI-based systems to facilitate various activities. This study examines how AI can simplify a company's work and help solve problems related to supply chain performance, thereby improving company performance with the support of information quality, information technology, and information sharing, which helps the smooth running of the supply chain for the advancement of the company. This research facilitates the identification of key problems and their effective and efficient resolution for issues that arise in companies. This research uses quantitative data obtained from a survey of the community in the city of Batam. The results obtained from the survey show that AI can simplify various aspects for companies. The results of the study show that the influence of information quality and information technology on supply chain performance through the application of information sharing has a significant effect. This study shows that using current technology can improve company performance. For current developments, the most important thing for companies is to utilize AI for technological advancement at this time.